Enhancing Arabic Language Learning Through CLIL in the MBKM Curriculum - Annova, Fauzana; Arifin, Zainul; Husna, Ilya; Banonah, Nabil Ahmed (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2025)
The transition from the Indonesian National Qualifications Framework (KKNI) to the Merdeka Belajar Kampus Merdeka (MBKM) curriculum introduces new challenges for Arabic language learning in higher education, particularly the need for flexible and integrative teaching approaches. This study explores the implementation of the Content and Language Integrated Learning (CLIL) approach within the MBKM framework. It examines its effects on students’ motivation and proficiency in reading and writing Arabic. Employing a quasi-experimental design with a non-equivalent control group, the sample consisted of an experimental group from class MPI-IA (38 students) and a control group from class MPI-IB (40 students). Data were collected through questionnaires, reading and writing tests, classroom observations, and semi-structured interviews and were analyzed using descriptive statistics and independent sample t-tests. The results demonstrate that the CLIL approach significantly enhances students’ motivation and Arabic language skills while also supporting a deeper understanding of Islamic education content through the integration of Arabic texts. These findings suggest that CLIL is a promising pedagogical strategy for aligning Arabic language instruction with the objectives of curriculum transformation and the development of interdisciplinary competencies.